Naratif Malaysia melalui perspektif Malik Bennabi - Ab Razak, Ratna Roshida (Penerbit Universiti Sultan Zainal Abidin, 2021)
Malaysia, which began to improve after the 14th General Election, was only allowed to last for 22 months. The government of Malaysia is now under a new administration known as the National Alliance. These shifts have led to a new political culture. This doesn't mean, however, that all national institutions need to be changed to display differences. The crucial thing is that the democratic changes being carried out are in a position to address the cultural, social and educational problems. The new dawn that illuminates Malaysia 's land today is expected to continue to provide the Malaysian society of diverse races and religions with peace and prosperity. . It is important that Malaysia has a new narrative in building every citizen 's ability to be a key player in the development and construction of Malaysian Civilization together, or more precisely in continuing the process of building Malaysian Civilization itself. Therefore, this paper aims to illustrate the ongoing phase of civilization building from the viewpoint of Malik Bennabi, an Algerian civilizational scholar.